2021
DOI: 10.1002/pc.25943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hygrothermal aging on chemical, physical, and mechanical properties of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate)/Cloisite 30B bionanocomposite

Abstract: Hygrothermal aging of neat poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and PHBV filled with an organomodified montmorillonite (C30B) at 3wt. was investigated at 65 C and 100% relative humidity (RH) up to 100 days. FT-IR data indicated that the carbonyl intensity index decreased with exposure time for both samples, while the main degradation mechanism occurred through hydrolysis reaction. This led to chain scissions resulting in a decrease in molar mass. Water absorption increased with exposure time for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It is expected that decrease in I 1718/1379 occurs because of hydrolytic degradation of PHBV during accelerated weathering. Iggui et al [ 31 ] have demonstrated that thedecrease in the carbonyl index because of hydrolytic aging is clearly related to the reduced molecular weight of PHBV.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that decrease in I 1718/1379 occurs because of hydrolytic degradation of PHBV during accelerated weathering. Iggui et al [ 31 ] have demonstrated that thedecrease in the carbonyl index because of hydrolytic aging is clearly related to the reduced molecular weight of PHBV.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate a drop in thermal stability due to the decrease in temperatures of % weight in all three sample groups after hydrothermal aging. The decline in thermal stability can be attributed to the synergetic effects of thermal and hydrolytic degradation 41 …”
Section: Resultsmentioning
confidence: 99%
“…The decline in thermal stability can be attributed to the synergetic effects of thermal and hydrolytic degradation. 41…”
Section: Thermal Analysis Resultsmentioning
confidence: 99%
“…The creep master isotherm was higher for dry specimens as compared to water aged specimens Daly et al [27] Numerical simulation of water absorption in Glass fiber reinforced composites Temperature inside aged specimens was constant and water diffusion followed Fick's law Albuquerque et al [28] Jute-roving reinforced polyester composites mechanical behavior with water absorption Mechanical properties were decreased with water immersion due oxidative degradation of both fiber and matrix Haddar et al [29] Glass fiber reinforced polyamide monotonic and cyclic load behavior with hygrothermal aging Fatigue life was severely decreased due moisture absorption. Water diffusion into polymer reduced the stress transmissibility Hong and Xian [30] Carbon fiber reinforced polyurethane plate Tensile properties of carbon fiber reinforced polyurethane plate were constant/enhanced as compared to epoxy based carbon fiber reinforce with moisture absorption Iggui et al [31] Poly/Cloisite 30B bionanocomposites behavior with water aging It was observed that mechanical properties decreased due to hydrolysis reaction resulting in chain scissions Jiang et al [32] Jute/Ploy (lactic acid) composites mechanical properties variation with alkaline and saline absorption Alkaline solution absorption and its effect on properties was higher than saline solution Manickam et al [33] Roselle fiber-vinyl ester composite mechanical behavior with moisture absorption Sea water absorption was more than other immersion environment Rubio-Gonzalez et al [34] Fiber-Multi-walled carbon nanotubes (MWCNT)/Polymer laminates moisture absorption effect under impact loading Impact resistance of wet specimens was lower than dry due plasticizing effect of the matrix Sahu and Gupta [35] Sisal/epoxy composite mechanical behavior with water absorption Sisal coating reduced the water absorption and mechanical properties were better than uncoated after immersion in water Delamination is the most severe threat to increased applications of composites in primary load bearing structures. [18] Improvement of fracture toughness to increase delamination resistance is extensively investigated in past few decades.…”
Section: Referencesmentioning
confidence: 99%
“…[25] In general, the water aging effect on mechanical properties of composites has been investigated for different composite materials ranging from natural fiber reinforced composite to high strength artificial fiber reinforced composites. [13,15,[21][22][23][26][27][28][29][30][31][32][33][34][35] The loading conditions included tensile, torsion, impact, fracture, and fatigue. In general, the mechanical properties of composite materials degraded with moisture absorption.…”
Section: Referencesmentioning
confidence: 99%